Volksrepublik China: Bauwerke der Liao-Zeit (907–1125) – Struktur, Geschichte, Erhalt - Wagner, Mayke; Schulz-Brize, Thekla; Wulf-Rheidt, Ulrike (e-Forschungsberichte des DAI, 2023)
The architecture of the empire Liao (907–1125) belongs to the oldest preserved wood constructions in China. The buildings embody valuable information on the development of the classical Chinese sacral architecture. They also contain sculptures and wall paintings of extraordinary importance. The Chinese Academy of Cultural Heritage already documented and restored one of the most famous temples, the Dule Temple, located between Peking and Tianjin. To make this authentic medieval building complex known in Germany is one of the concerns of the Beijing Branch of the German Archaeological Institute. In the Fengguo Temple complex in Liaoning Province measures of restoration and preservation of the unique wood construction and wall paintings are urgently needed. On invitation of the local heritage protection authorities the team visited the Fengguo Temple and jointly developed a tentative work plan.